Monitoring reservoir water elevation changes using Jason-2/3 altimetry satellite missions: exploring the capabilities of JASTER (Jason-2/3 Altimetry Stand-Alone Tool for Enhanced Research) - Natalya Ross; Amirhossein Rostami; Hyongki Lee; Chi-Hung Chang; Faisal Hossain; Pietro Milillo; Tien L. T. Du; Susantha Jayasinghe; Peeranan Towashiraporn (International Journal of Digital Earth)
In the absence of in-situ data, satellite radar altimetry, critical for studies requiring water elevation data, faces challenges in outlier removal over reservoirs, influenced by surrounding land. We present JASTER (Jason Altimetry Stand-Alone Tool for Enhanced Research), an open-source, fully automated tool processing Jason-2/3 altimetry data for water elevation time series generation over a user-defined inland water body. JASTER uses two outlier removal approaches. The first method employs interquartile range (IQR)-based filtering and K-means clustering. The second method incorporates water occurrence (WO) and Digital Elevation Model (DEM)-derived elevation thresholds. The Hampel filter embedded in JASTER further removes non-physical peaks in the time series caused by signal noise. We validated JASTER’s capabilities using 44 Jason altimeter crossings over 37 water bodies in the US and Canada. We assessed the significance of applying water occurrence and elevation thresholds, and investigated how the Hampel filter parameters and satellite crossing lengths affect accuracy. In all case studies, the Hampel filter significantly increased the consistency between JASTER-derived water elevations and in-situ data. Moreover, the DEM + WO-based method outperformed the IQR-based outlier removal approach in some cases where the greater number of altimeter footprints belonged to land instead of water.